2019
DOI: 10.3389/fphar.2019.00488
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Inhibition of Tumorigenesis Using Combinations of miRNA-Targeted Therapeutics

Abstract: The search for effective strategies to inhibit tumorigenesis remains one of the most relevant scientific challenges. Among the most promising approaches is the direct modulation of the function of short non-coding RNAs, particularly miRNAs. These molecules are propitious targets for anticancer therapy, since they perform key regulatory roles in a variety of signaling cascades related to cell proliferation, apoptosis, migration, and invasion. The development of pathological states is often associated with dereg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 152 publications
(241 reference statements)
0
45
0
Order By: Relevance
“…Based on in silico research by Nurasih et al, (2018) miR-324-5p targeting GLI1 through Hedgehog signaling pathway. Miroshnichenko et al, (2019) demonstrated the success of miRNA-based therapy combined with chemotherapy drugs to inhibit tumor development. Recent studies have shown a considerable increase in the efficacy of anticancer therapy as a synergistic effect of the therapy being applied simultaneously.…”
Section: Research Articlementioning
confidence: 99%
“…Based on in silico research by Nurasih et al, (2018) miR-324-5p targeting GLI1 through Hedgehog signaling pathway. Miroshnichenko et al, (2019) demonstrated the success of miRNA-based therapy combined with chemotherapy drugs to inhibit tumor development. Recent studies have shown a considerable increase in the efficacy of anticancer therapy as a synergistic effect of the therapy being applied simultaneously.…”
Section: Research Articlementioning
confidence: 99%
“…Modulating of miRNA levels or restoring their function may be a new strategy in the cancer treatment. There are two ways to modulate the level of a particular miRNA: restoration of tumor suppressor miRNA by a straightforward transfection of synthetic mimics or transduction of cells with vectors expressing miRNAs (Miroshnichenko & Patutina, 2019). On the other hand, new technologies have been developed to inhibit functions of oncogenic miRNAs.…”
Section: Micrornas As Biomarkers and Therapeutics In Cancermentioning
confidence: 99%
“…On the other hand, new technologies have been developed to inhibit functions of oncogenic miRNAs. Such compounds may target the miRNA sequence or interrupt the miRNA regulatory activity through interaction with their mRNA targets (Miroshnichenko & Patutina, 2019). Modulation of the miRNAs' level may be used to directly target tumor cells or it may also enhance other therapies, which has been shown in small cell lung cancer for miR-100 that regulated chemo-resistant properties of cancer cells (Xiao et al, 2014).…”
Section: Micrornas As Biomarkers and Therapeutics In Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs) are abundant class of non-coding 18-25 nucleotide small RNAs, which bind to the 3'-UTR of specific target mRNAs to suppress gene expression, either via inducing translational inhibition or mRNA degradation (Ricciuti et al, 2014;Abu-Duhier et al, 2018;Amri et al, 2019). MiRNAs participate in a variety of biological processes, such as cell cycle progression, proliferation, growth and apoptosis (Zhang et al, 2014;Fatima et al, 2019;Miroshnichenko and Patutina, 2019). Aberrant expression of particular miRNAs is a hallmark of many human tumor types, including NSCLC, and they can act as either oncogenes or as tumor suppressors (Zhao et al, 2013;MacDonagh et al, 2015;Yin et al, 2017;Bharali et al, 2018).…”
Section: Introductionmentioning
confidence: 99%